How to choose when implants of adjacent height both fit the disc space properly in single-level cervical artificial disc replacement. Issue 29 (July 2017) - Rong, Xin; Lou, Jigang; Li, Huibo; Meng, Yang; Liu, Hao
Abstract : Abstract: In cervical artificial disc replacement (C-ADR), sometimes we encountered with such cases that implants of adjacent height both fit the target disc space properly. No study was available discussing the choice of implant height and the clinical outcomes under such circumstance. The purpose of this study was to evaluate the impact of different implant heights on the clinical outcomes and radiographic results when the implants of adjacent height both fit the disc space properly. This retrospective study included 34 patients underwent single-level C-ADR at the C5–C6 level at our institution. In these 34 patients, implant with either 5 mm height or 6 mm height fit the surgical level properly without overstretching the disc space or the facet joint space. Clinical outcomes were evaluated using the Japanese Orthopedic Association score, visual analog scale (VAS), and Neck Disability Index. Radiographic assessments were conducted on static and dynamic radiographs for the determination of the disc space height, intersegmental range of motion (ROM), and the ROM of the functional spinal unit (FSU) at the surgical level. The baseline information of the patients, such as age, gender, weight, follow-up time, and diagnosis, was similar between the 2 groups ( P  > .05). Postoperative mean VAS in group B was significantly lower than that in group A (2.1 ± 0.7 vs. 2.7 ± 1.0, P  < .05). The mean VAS decrease in group B was significantly larger than that in group A (5.3 ± 0.8 vs. 4.6 ± 1.1, P  < .05). Significant difference was found in the postoperative disc height of the surgical segment between the 2 groups (6.4 ± 0.4 mm vs. 7.5 ± 0.5 mm, P  < .05). No significant differences were noted in the intersegmental ROM and ROM of the FSU between the 2 groups both before the surgery and at the last follow-up ( P  > .05). No hypermobility or instability was observed in these patients. Our results suggested that when implants of adjacent height both fit the disc space properly, using the larger implant could result in better pain relief without the risk of segmental hypermobility in patients underwent single-level C-ADR at the C5–C6 level.